Consistency of temperament traits and their relationships with milk yield in lactating primiparous F1 Holstein - Gyr cows - Marcal-Pedroza, Maria G.; Campos, Mariana M.; Pereira, Luiz Gustavo R.; Machado, Fernanda S.; Tomich, Thierry R.; Paranhos da Costa, Mateus J. R. [UNESP]; Sant'Anna, Aline C. [UNESP] (Elsevier B.V., 2020)
The objectives of the present study were: a) to evaluate the consistency of temperament traits of primiparous F1 Holstein - Gyr cows throughout time and across distinct handling situations (milking temperament and handling temperament in the corral), and b) to assess the relationships between temperament traits and milk yield. The milking temperament was characterized by the movement of the hind legs (number of steps and kicks), in addition to recording the frequencies of defecation, urination, rumination and kicking off the milking cluster, as well as recording individual daily milk yield. To evaluate handling temperament in the corral, the following data were recorded: ET (entrance time, time to walk along the single-file race and enter the squeeze chute); CS (crush score, assessing the reactivity within the squeeze chute, in scores from 11 = no movement to 4 = frequent and vigorous movements); FS (flight speed); FD (flight distance) and NOT (novel object test, recording latency for the animal to interact with an unfamiliar object). The number of steps during milking was negatively correlated with ET (r = - 0.285; P < 0.01) and positively with FS (r = 0.355; P < 0.01), FD (r = 0.245; P < 0.05) and NOT (r = 0.283; P < 0.05), indicating that the animals which took a greater number of STEPS during milking were faster to enter and exit the squeeze chute, kept a greater distance from the observer and were more cautious to interact with the novel object. In turn, the frequency of kicking off the milking cluster was positively correlated with ET (r = 0.230; P < 0.05) and CS (r = 0.322; P < 0.01), but negatively with NOT (r = - 0.386; P < 0.01), indicating that the animals that kicked off the milking cluster were more reactive in the chute and had a greater disposition to interact with the novel object. Milk yield was negatively correlated with the number of KICKS (r = - 0.244; P < 0.05) and positively with the rumination (r = 0.324; P < 0.01). Rumination was the only behavioural trait with effect on the milk yield (F-2,F-78 = 4.02; P < 0.05). The temperament of crossed Holstein-Gyr dairy cows was consistent over time and through the different handling situations and milking temperament traits were associated with milk yield, unlike handling temperament.
Keywords: Behaviour; Daily cattle; Handling; Reactivity; Zebu cattle